Mutal Burkhanov has Been in the World of Uzbek Music Place - Farangiz Ikromova (Genius Journals, 2022)
In this article, detailed information is given about the importance of the rich heritage of the composer, artist, creative artist Mutal Burkhanov in the culture of Uzbek music and how he skilfully reworked folk songs
Keywords: folk songs; romance; acapella; romance-poem